2022
DOI: 10.21203/rs.3.rs-1892415/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Efficacy of Insect Endogeneous Cellulases for Ligno-cellulosic Biofuels Deciphered Using Molecular Docking Studies

Abstract: Cellulose, the substance that makes up most of a plant’s cell wall, is pondered to be one of the most abundant natural organic polymers on earth made up of glucose units linked by β-1, 4 glycosidic bonds. Insects possess cellulolytic system capable of producing variegate enzymes with multifarious specificities to break down complex lignocellulosic products. Astonishingly, endoglucanases, exoglucanase, and β-glycosidases act sequentially in a synergistic system to facilitate the breakdown of cellulose to utiliz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Willis et al (2011) reported the first endoglucanase from an insect model organism Tribolium castaneum . The order Coleoptera has been identified with the occurrence of endogenous cellulases, especially many endoglucanases have been studied exclusively in this insect order (Bhuvaragavan et al, 2019; Nivetha et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Willis et al (2011) reported the first endoglucanase from an insect model organism Tribolium castaneum . The order Coleoptera has been identified with the occurrence of endogenous cellulases, especially many endoglucanases have been studied exclusively in this insect order (Bhuvaragavan et al, 2019; Nivetha et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…with the occurrence of endogenous cellulases, especially many endoglucanases have been studied exclusively in this insect order (Bhuvaragavan et al, 2019;Nivetha et al, 2022).…”
Section: Discussionmentioning
confidence: 99%